Kemandirian Antara Santriwati Mukim dan Santriwati Non Mukim di Pondok Pesantren Al-Falah Puteri - Arianti, Susan; Mulyani, Mulyani; Hairina, Yulia (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2022)
Independence is the readiness and ability of individuals to stand alone marked by being able to make their own decisions, trying to solve problems without the help of others, trying to direct behavior towards goodness and perfection, being able to take the initiative to solve problems, being able to control thoughts, actions, feelings freely. , as well as trying to overcome shame and self-doubt on their own. This study aims to determine the difference in independence between mukim and non-mukim students at the Al-Falah Islamic Boarding School Puteri Banjarbaru. This study uses quantitative research methods. The population is students of class 2 Tsanawiyah totaling 60 respondents consisting of 30 mukim students and 30 non-mukim students. The sampling technique used is purposive sampling. The results showed that there was no significant difference in independence between mukim and non-mukim students at the Al-Falah Islamic Boarding School Puteri Banjarbaru, the sig.2-tailed hypothesis was (0.139 > 0.05). Mukim students who have a moderate level of independence (36.6%) are more than mukim students who have a low level of independence. Especially for mukim students with low levels of independence, most of them are due to lack of self-confidence to express opinions. Then non-mukim female students who have a moderate level of independence (38.3%) are more than non-mukim female students who have a low level of independence. Especially for non-mukim female students with low levels of independence, the causes are dominated by shyness, lack of confidence and hesitation in making decisions.